THE ASSOCIATION BETWEEN THE NUTRITIONAL STATUS OF PREGNANT WOMEN AND HYPERTENSIVE DISORDERS IN PREGNANCY AT PUSKESMAS SUKASADA I - Luh Kadek Vidya Dita Parami; Ni Putu Dewi Sri Wahyuni; Putu Sudarsana (Universitas Pahlawan Tuanku Tambusai, 2025)
Hypertension disorders during pregnancy remains a major contributor to maternal mortality in Indonesia in 2022 and the third in Bali in 2023. One factor contributing to hypertension during pregnancy is nutritional status. This research aims to examine the association between nutritional status of pregnant women and hypertensive disorders in pregnancy at Puskesmas Sukasada I as an effort to understand the determinants of healthy behavior and the prevention of pregnancy complications. A quantitative descriptive study was conducted using a cross-sectional analytical design. Data collection used simple random sampling of pregnant women attending Antenatal Care at the Mother and Child Clinic of the Puskesmas Sukasada I (N=50). The research instrument used medical records analyzed using the Pearson Chi-square method. Bivariate analysis using the Pearson Chi-square test obtained a p-value of 0.376, which indicates that there is no statistically significant relationship between nutritional status and hypertensive disorders in pregnancy at Puskesmas Sukasada I during the 2023–2024 period. Hypertensive disorders in Pregnancy is caused by multiple factors, not just nutritional status. Therefore, maintaining optimal nutrition along with addressing other modifiable factors remains essential in preventing hypertensive disorders and supporting healthy pregnancy outcomes.